Harmonization of Next-Generation Sequencing Procedure in Italian Laboratories: A Multi-Institutional Evaluation of the SiRe® Panel - Malapelle, Umberto; Pepe, Francesco; Pisapia, Pasquale; Sgariglia, Roberta; Nacchio, Mariantonia; De Luca, Caterina; Lacalamita, Rosanna; Tommasi, Stefania; Pinto, Rosamaria; Palomba, Grazia; Palmieri, Giuseppe; Vacirca, Davide; et al. (Frontiers in Oncology, 2020)
Background: Next generation sequencing (NGS) needs to be validated and standardized to ensure that cancer patients are reliable selected for target treatments. In Italy, NGS is performed in several institutions and harmonization of wet and dry procedures is needed. To this end, a consortium of five different laboratories, covering most part of the Italian peninsula, was constituted. A narrow gene panel (SiRe®) covering 568 clinically relevant mutations in six different genes (EGFR, KRAS, NRAS, BRAF, cKIT and PDGFRα) with a predictive role for therapy selection in non small cell lung cancer (NSCLC), gastrointestinal stromal tumor, colorectal carcinoma (CRC) and melanoma, was evaluated in each participating laboratory. Methods: To assess the NGS inter – laboratory concordance, the SiRe® panel, with a relative kit and protocol for libraries preparation, was used in each center to analyze a common set of 20 NSCLC and CRC routine samples. Concordance rate in terms of mutation detected and relative allelic frequencies was assessed. Then, each institution prospectively analyzed an additional set of 40 routine samples (for a total of 160 specimens) to assess the reproducibility of the NGS run parameters in each institution. Results: An inter – laboratory agreement of 100% was reached analyzing the data obtained from the 20 common sample set; the concordance rate of allelic frequencies distribution was 0.989. The prospective analysis of the run metric parameters obtained by each center locally showed that the analytical performance of SiRe® panel in different institutions was highly reproducible. Conclusions: SiRe® panel represents a robust diagnostic tool to harmonize NGS procedure in different Italian laboratories.